Determinant of Islamic Corporate Social Responsibility (ICSR) Disclosure in Companies Registered in Jakarta Islamic Index (JII) - Isman, Ainul Fatha; Aeni, Nur Cholifatul (Faculty of Islamic Economics and Business, Madura Islamic State University, 2021)
Social aspects are important aspects that must be considered by every individual. Similarly, companies that must disclose social responsibility or what is called Corporate Social Responsibility (CSR) through the mandate of the Act. This research aims to determine the factors that affect the Islamic corporate social responsibility disclosure in Indonesia. This research is categorized in quantitative research with associative approaches. The population in this study amounted to 30 companies registered in the Jakarta Islamic Index in 2016-2018 with a purposive sampling technique to obtain 51 samples. The data analysis model in this study is a panel data linear regression test with a combination of time series data and cross-section which is carried out through three approaches, namely the common effect model, the fixed-effect model, and the random effect model. The results of this study indicate that partially and simultaneously the size of the company's profitability, and the Muslim board of directors influence the disclosure of the company's ICSR. The most influential factor in company ICSR disclosure is company size. The results of this study imply that each company uses the ISR Index as a reference for the preparation of sharia corporate social responsibility reporting standards and increases the number of Muslim board of directors who are competent and have innovative ideas to increase company assets, thus positively impacting ICSR disclosure.